PREVALANCE OF PPROM AND ITS OUTCOME - Noor, Shehla; Nazar, Ali Fawwad; Bashir, Rubina; Sultana, Ruqqia (Journal of Ayub Medical College Abbottabad, 2007)
Background: Prematurity is the leading cause of perinatal morbidity and mortality in developed as well as in underdeveloped countries. In one third of the patients with preterm labour there is associated premature rupture of membranes. This prospective observational study was carried out in Ayub Teaching Hospital to determine the prevalence of preterm premature rupture of membrane (PPROM) and its association with the demographic risk factors and its outcome. Method: There were 889 deliveries in Gynaecology '˜C' unit from September 2005 to March 2006. Out of these, 85 patients were confirmed to have PPROM. Detail history and examination along with the demographic risk factors were recorded on a performa. Every patient was followed till her delivery and the mode of delivery and maternal and foetal outcome was recorded. Result: Prevalence of PPROM in this study was 16%. It was seen to be common among patients who were young (15-25 years) 58.8%, with low socioeconomic status (68.2%), and with an educational status of primary to middle (71.7%). Risk of PPROM was seen to be highest among patients giving birth to their first child (42.2%), with gestational age between 30-35 weeks (43.5% cases) and 35-37 weeks (35.2%). In 69.4% cases there was no previous history of preterm deliveries while in 30.6% cases, there were one, two, or more previous preterm deliveries. Normal vaginal delivery occurred in (65.86%), while instrumental delivery rate in PPROM was 20% and caesarean section rate was 14%. Postnatally 16.47% patients developed infection while 24 (28.2%) babies developed infection and required antibiotics. Majority of babies born to patients with PPROM were low birth weight (62.3%), and 30.5% babies required neonatal intensive care. Perinatal mortality rate was 129.9/1000 (13%) of total births. Conclusion: PPROM is an important cause of preterm birth, resulting in large number of babies with low birth weight, requiring neonatal intensive care. It is associated with increased foetal morbidity and mortality. Demographic variables can be applied to develop risk scoring so as to identify high-risk cases and treating them in time to prevent ascending infection along with its complications. Key words: Preterm premature rupture of membrane, PPROM, preterm birth